USM STRENGTHENS LEADERSHIP CAPACITY OF GLOBAL POSTGRADUATES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, August 2015 Universiti Sains Malaysia (USM) is stepping ahead in strengthening the leadership capacity of its postgraduate students through the Asia Pacific Alliance of Postgraduate Student Association (APAPSA) for Leadership and Community Work for the second time, attracting participation of students from countries in the AsiaPacific region.